Endophthalmitis Following Strabismus Surgery: IPOSC Global Study. (2nd December 2017) - Zloto, Ofira; Mezer, Eedy; Ospina, Luis; Stankovic, Branislav; Wygnanski-Jaffe, Tamara
ABSTRACT: Purpose : To examine the characteristics of patients with endophthalmitis after strabismus surgery (PSSE), the characteristics of the strabismus surgery, treatment, and prognosis as reported by pediatric ophthalmologists who are members of the American Association for Pediatric Ophthalmology and Strabismus (AAOPS) around the world. Methods : An email communication was sent to all members of AAPOS. The email included a web link to a survey that included 34 questions that examined the characteristics of patients with endophthalmitis after strabismus surgery. Results : Three hundred forty-nine ophthalmologists responded to the questionnaire. Two hundred sixty four (76%) had practiced pediatric ophthalmology for over 10 years. Twenty-seven cases of endophthalmitis were reported. The medial rectus muscle (MR) was the most common muscle undergoing surgery (55%). In 5 patients (21%), perforation was observed at the time of surgery. In all cases, endophthalmitis was diagnosed 3–7 days after surgery. The final visual acuity of 34% was no light perception (NLP). Discussion : This series is the largest existing series on PSSE. Our data suggest that PSSE can occur also in healthy patients and in patients without a visualized scleral perforation. The majority of PSSE occurs during the first week after surgery. Therefore, we believe that all patients that underwent strabismus surgery should be examined in this time frame. The prognosis was poor with 48% demonstrating a visual acuity of LP or NLP at the final follow-up.